Inequalities in non-communicable diseases across the European Union: current state and trends from 2000 to 2019. (20th October 2021) - Peñalvo, JL; Mertens, E; Devleeschauwer, B; Grad, DA; Hrzic, R; Bikbov, B; Abbafati, C; Balaj, M; Cuschieri, S; Eikemo, TA; Fischer, F; Ghith, N; et al.
Abstract: Background: Non-communicable diseases (NCDs) remain the leading cause of disease burden in the European Union (EU). However, this burden varies across Member States, driven by the socioeconomic and demographic structure of the populations, as well as health care and social support systems in each country. This geographical gradient in the burden of NCDs represents health inequalities that may have expanded as a result of population ageing, migration, and economic crisis, and historic backgrounds. Methods: Using data from the GBD 2019 study, we quantify the inequality gap between EU countries, characterize the geographical gradient of total and individual NCDs, and analyze the trends over the last 20 years. Results: A considerable gap exists in the rates of NCD-related DALYs between the country with the lowest burden (Slovenia in 2019) and the highest (Bulgaria in 2019), with a constant (p-trend > 0.05) ratio of 1.6 (95%CI, 1.57; 1.64) since the year 2000. The largest inequality was observed for the burden of stroke between the lowest (France in 2019) and the highest (Bulgaria in 2019) with a ratio of 7.47 (6.78; 8.24) Increasing steadily (p-trend < 0.001) since 2000. Using the relative index of inequality to characterize the gradient of inequalities across the EU, a decreasing trend (p < 0.001) can be observed for NCD-related DALYs rates from 1.56 (1.44; 1.7) in 2000 to in 1.42 (1.33; 1.52) 2019. Conclusions: Despite overall improvements in health, spatial disparities related to NCDs in the EU persist. Our estimates provide a baseline to inform future equitable health policies.